Pelatihan dan Sosialisasi Pupuk Plant Growth Promoting Rhizobacteria (PGPR) pada KWT di Desa Wilayu, Kecamatan Selomerto, Kabupaten Wonosobo - Talia, Naila Arzaq; Irfana, Ita Isna; Hakim, Muhammad Faishal; Solikah, Siti Nur; Riandra, Ilham; Armanda, Dian Triastari (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
increase production costs and reduce soil quality. Members of the Women Farmers Group in Wilayu Village still rely heavily on synthetic chemical fertilizers for rice, vegetables, and horticultural crops, despite the negative impacts on soil and the environment. To address this issue, a community service activity was conducted in the form of training and socialization on the production of biofertilizers based on plant growth-promoting bacteria. This activity aimed to improve the knowledge and skills of the Women Farmers Group in producing and utilizing biofertilizers from bamboo roots as an environmentally friendly alternative. The methods applied included structured socialization, lectures, hands-on practice using simple materials from the local environment, and question-and-answer and discussion sessions. The results showed an increase in the knowledge and skills of members in producing biofertilizers, enabling them to reduce dependency on synthetic chemical fertilizers, implement environmentally friendly farming practices, improve the quality and added value of agricultural products, reduce production costs, and enhance the independence and welfare of members. The activity also raised awareness of the importance of sustainable agricultural innovation by utilizing local potential, particularly bamboo roots as a source of biofertilizer.